Versican—A Critical Extracellular Matrix Regulator of Immunity and Inflammation - Wight, Thomas N.; Kang, Inkyung; Evanko, Stephen P.; Harten, Ingrid A.; Chang, Mary Y.; Pearce, Oliver M. T.; Allen, Carys E.; Frevert, Charles W. (Frontiers in Immunology, 2020)
The extracellular matrix (ECM) proteoglycan, versican increases along with other ECM versican binding molecules such as hyaluronan, tumor necrosis factor stimulated gene-6 (TSG-6), and inter alpha trypsin inhibitor (IαI) during inflammation in a number of different diseases such as cardiovascular and lung disease, autoimmune diseases, and several different cancers. These interactions form stable scaffolds which can act as “landing strips” for inflammatory cells as they invade tissue from the circulation. The increase in versican is often coincident with the invasion of leukocytes early in the inflammatory process. Versican interacts with inflammatory cells either indirectly via hyaluronan or directly via receptors such as CD44, P-selectin glycoprotein ligand-1 (PSGL-1), and toll-like receptors (TLRs) present on the surface of immune and non-immune cells. These interactions activate signaling pathways that promote the synthesis and secretion of inflammatory cytokines such as TNFα, IL-6, and NFκB. Versican also influences inflammation by interacting with a variety of growth factors and cytokines involved in regulating inflammation thereby influencing their bioavailability and bioactivity. Versican is produced by multiple cell types involved in the inflammatory process. Conditional total knockout of versican in a mouse model of lung inflammation demonstrated significant reduction in leukocyte invasion into the lung and reduced inflammatory cytokine expression. While versican produced by stromal cells tends to be pro-inflammatory, versican expressed by myeloid cells can create anti-inflammatory and immunosuppressive microenvironments. Inflammation in the tumor microenvironment often contains elevated levels of versican. Perturbing the accumulation of versican in tumors can inhibit inflammation and tumor progression in some cancers. Thus versican, as a component of the ECM impacts immunity and inflammation through regulating immune cell trafficking and activation. Versican is emerging as a potential target in the control of inflammation in a number of different diseases.